The Effect of gadget on the development of children during pandemic covid-19 situation - Safarina Febriani; Moses Glorino Rumambo Pandin (Universitas Ahmad Dahlan, 2021)
Covid-19 has brought many changes in our lives. One of them is the widespread use of gadgets in early childhood. Because learning is held online where their teachers at school should give children or students material, now they understand the material via smartphones or gadgets. Of course, it makes them less understanding of what is being said. It feels bored because it is not interesting. Their learning time is filled with entertainment such as playing games, watching videos, accessing social media, even to the point of addiction and forgetting time. Therefore, this article will discuss the use of gadgets, the impact on children, and how to take further actions to balance children's understanding between learning and playing.